CARACTERIZAÇÃO MOLECULAR DO GENE VHL ASSOCIADO À SÍNDROME VON HIPPEL LINDAU EM UMA FAMÍLIA AFRODESCENDENTE COM HEMANGIOBLASTOMA DE SISTEMA NERVOSO CENTRAL NO ESTADO DO MARANHÃO - AZEVEDO, Patrícia Ribeiro (2013)
The von Hippel Lindau syndrome (VHL) is an autosomal dominant disorder with an incidence of 1:36.000 to 1:53.000 individuals, characterized by multiple tumors, affecting individuals of twenty and forty years, with life expectancy of 60 years. The objective of this study was to characterize the molecular changes in the VHL gene associated with von Hippel Lindau syndrome in a family of African descent with hemangioblastoma of the central nervous system in the state of Maranhão. For investigation of the family history, all family members were interviewed, and performed molecular analysis of seven patients with clinical diagnosis of VHL and 89 family members at risk. For DNA extraction was used peripheral blood. The technique used was the amplification of multiplex ligation probes dependent binding (MLPA). After PCR- MLPA, was performed sequencing and the software GeneMaker was used for screening of mutations. The research followed the ethical precepts. We investigated the family history of the eight individuals of African descent carriers hemangioblastomas of the central nervous system. In addition to this injury, these individuals had retinal hemangioblastoma, pancreatic cyst and bilateral kidney tumor. The average age of first presentation of the lesion was 29 years, not having occurred predominantly in relation to gender. In the screening protocol was not evidenced pheochromocytoma. No injuries were surveyed in the reproductive system because of the absence of symptoms. The molecular test detected the deletion c.1-? _340 +? in all symptomatic individuals and 14 family members. The MLPA, technique has proven to be fast and reliable for diagnosis of large deletions. A positive family history, the absence of pheochromocytoma and detection of genomic deletion of exon 1, allowed the clinical diagnosis and molecular VHL syndrome and classification as type 1. In this study it was possible to evaluate, in addition to the proband, other family members. This approach decreases the morbidity of the disease and provides a better quality of life for families.